Self-oscillations of concentrations of unsaturated compounds in the oxidative carbonylation processes. 2. Oxidative carbonylation of alkynes in solutions of palladium halide complexes - N. S. Gorodsky (Тонкие химические технологии, 2011)
This review is devoted to studying the results of concentration oscillations phenomena observed in unsaturated compounds oxidative carbonylation. These homogeneous reactions are catalyzed by metal complexes. The second part of the review is devoted to describing various alkynes oxidative carbonylation, which can occur in oscillation mode. The main results of mathematic modeling of the studied systems are described.